Binocular visual field in adults with horizontal strabismus and driving requirements - Alfaqawi, Fadi; Young, Jane; Kaye, Stephen B (Eye (London), 2023)
To determine the horizontal extent of the binocular visual field (BVF) in subjects with horizontal strabismus and whether the BVF falls below the driving standard. Adults with congenital esotropia and infantile exotropia ≤45 Prism Dioptres (PD), and subjects with orthotropia were recruited. The manifest angle of deviation was measured using a simultaneous prism cover test. Monocular Visual Field (MVF) and BVF were measured using the Esterman visual field test. Subjects with diplopia or a manifest angle of strabismus that varied by>8PD or the present of a vertical tropia >8PD were excluded. Forty-nine subjects were included: 10 with orthotropia, 20 with exotropia and 19 with esotropia. The horizontal extent of BVF (degrees) was significantly smaller in esotropes (122.8 ± 18.8) than in orthotropes (141 ± 6.6) or exotropes (138.3 ± 8.3) (p < 0.01). In 6 (31.6%) subjects with an esotropia, the BVF was below the driving standard. The horizontal extent of the visual field (VF) of the amblyopic eyes of patients with esotropia (98.70 degrees, SD 19.76) and exotropia (104.75 degrees, SD16.93) were significantly smaller than those with orthotropia (121.00 degrees SD 3.16) by 22.3 degrees (p = 0.004) and 16.25 degrees (p = 0.045), respectively. The difference between the summation of MVFs and the BVF was significantly greater in orthotropes (100.6 ± 2.7) than in exotropes (68.9 ± 34.4) and esotropes (74.2 ± 20.7) (p < 0.01). The horizontal extent of BVF is significantly smaller and more variable in adults with congenital esotropia and may fall below the driving standard. Largest study on visual fields in subjects with horizontal strabismus including an orthotropic control group who do not have diplopia and who would otherwise meet the driving standard. Visual field quality was high but limitation is that visual field repeatability was not undertaken. The findings of this study would suggest that people with an esotropia should be offered the opportunity to have a binocular visual field test before applying for a driving license. The DVLA may want to consider requesting people with an esotropia to have a binocular visual field test as is a requirement with other ophthalmic conditions such as glaucoma.